Integrating interaction resources in the graphics clusters - La Marca, Anthony Ferreira [UNESP]; Dias, Diego Roberto Colombo [UNESP]; Ricci, Caio Cesar Pires [UNESP]; Brega, José Remo Ferreira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This paper aims to describe the basic concepts and necessary for Java programs can invoke libraries of programming language C/C ++, through the JNA API. We used a library developed in C/C ++ called Glass [8], which offers a solution for viewing 3D graphics, using graphics clusters, reducing the cost of viewing. The purpose of the work is to interact with the humanoid developed using Java, which makes movements of LIBRAS language for the deaf, as Glass's, so that through this they can view the information using stereoscopic multi-view in full size. ©2010 IEEE.
Keywords: LIBRAS; Multi-view; Virtual humans; 3D graphics; Basic concepts; Java program; Multi-views; Programming language; Application programming interfaces (API); Computer software; Glass; Java programming language; Virtual reality